Qui manet in amicitia manet in Deo: Friendship in a Latin Christian tradition - Krishna, Robert (Pacifica, 2016)
I explore the discourse on friendship in four Latin Christian authors, Ambrose of Milan, Augustine of Hippo, John Cassian and Aelred of Rievaulx, and how it occurs in the intersection of Cicero and biblical models and maxims. I conclude that friendship is not only central to the authors’ view of a fulfilled human life, but also to their understanding of the relationship between God and human beings.